Staged Repair of a Ruptured Thoracic Aortic Aneurysm Having an Aorto-Parenchymal Fistula. Issue 5 (September 2017) - Yoshitake, Akihiro; Okamoto, Kazuma; Kasai, Mio; Shimizu, Hideyuki
Abstract : Abstract: Ruptured thoracic aortic aneurysms, having aorto-bronchial or pulmonary parenchymal fistulations, are life-threatening conditions, and current surgical treatment results are not satisfactory. Herein, we describe a 69-year-old man with a ruptured thoracic aortic aneurysm and aorto-pulmonary parenchymal fistulation that was successfully treated using a staged repair. The first stage involved an emergency thoracic endovascular aortic repair for salvage and the second stage involved radical pulmonary parenchymal repair with removal of the stent graft and aortic reconstruction for long-term survival. Abstract : Supplemental digital content is available in the text.